Endometrium-derived mesenchymal stem cells suppress progression of endometrial cancer via the DKK1-Wnt/β-catenin signaling pathway - Yuhui Xu; Jiali Hu; Qiaoying Lv; Chenyi Shi; Mengdi Qiu; Liying Xie; Wei Liu; Bingyi Yang; Weiwei Shan; Yali Cheng; Bing Zhao; Xiaojun Chen (Stem Cell Research & Therapy, 2023)
Abstract Background Mesenchymal stem cell (MSC) therapy is an attractive treatment option for various cancers. Whether MSCs can be used to treat well-differentiated endometrial cancer (EC) remains unclear. The aim of this study is to explore the potential therapeutic effects of MSCs on EC and the underlying mechanisms. Methods The effects of adipose-derived MSCs (AD-MSCs), umbilical-cord-derived MSCs (UC-MSCs), and endometrium-derived MSCs (eMSCs) on the malignant behaviors of EC cells were explored via in vitro and in vivo experiments. Three EC models, including patient-derived EC organoid lines, EC cell lines, and EC xenograft model in female BALB/C nude mice, were used for this study. The effects of MSCs on EC cell proliferation, apoptosis, migration, and the growth of xenograft tumors were evaluated. The potential mechanisms by which eMSCs inhibit EC cell proliferation and stemness were explored by regulating DKK1 expression in eMSCs or Wnt signaling in EC cells. Results Our results showed that eMSCs had the highest inhibitory effect on EC cell viability, and EC xenograft tumor growth in mice compared to AD-MSCs and UC-MSCs. Conditioned medium (CM) obtained from eMSCs significantly suppressed the sphere-forming ability and stemness-related gene expression of EC cells. In comparison to AD-MSCs and UC-MSCs, eMSCs had the highest level of Dickkopf-related protein 1 (DKK1) secretion. Mechanistically, eMSCs inhibited Wnt/β-catenin signaling in EC cells via secretion of DKK1, and eMSCs suppressed EC cell viability and stemness through DKK1-Wnt/β-catenin signaling. Additionally, the combination of eMSCs and medroxyprogesterone acetate (MPA) significantly inhibited the viability of EC organoids and EC cells compared with eMSCs or MPA alone. Conclusions The eMSCs, but not AD-MSCs or UC-MSCs, could suppress the malignant behaviors of EC both in vivo and in vitro via inhibiting the Wnt/β-catenin signaling pathway by secreting DKK1. The combination of eMSCs and MPA effectively inhibited EC growth, indicating that eMSCs may potentially be a new therapeutic strategy for young EC patients desiring for fertility preservation.